Color Doppler ultrasonography in full term neonates with hypoxic ischemic encephalopathy and prediction of outcome - Naglaa Fathy Barseem; Hassan Said Badr; Mohamed Shawky Abdullah (SpringerOpen, 2016)
Background: Impaired cerebral circulation plays the main role in the pathogenesis of hypoxic-ischemic brain injury in neonates. Objectives: We aimed to determine blood flow parameters via color Doppler ultrasonography in full-term neonates with hypoxic-ischemic (HI) brain injury at 12 h postpartum and the correlation of these parameters with long-term outcomes at the age of 1-year. Design and subjects: Our study included 40 full term neonates with HIE (Patients group) and 25 healthy full term neonates (control group). All neonates were subjected to early color Doppler ultrasonography. At the age of 1-year the neurodevelopmental condition was evaluated. Results: The end-diastolic velocity (EDV) and peak systolic velocity (PSV) PSV values of cerebral arteries of patient group were significantly lower than those of the control group. Resistive index (RI) values were significantly higher in patient group than in the control group (P < 0.05). The values obtained from right and left anterior and middle cerebral arteries of patients and controls were significantly correlated (P < 0.05). During follow up of these cases, seven died in NICU, eleven were found to have neurodevelopmental sequelae and twenty-two were found to be normal. In comparison between neonates with good prognosis (No. 22) and those of poor prognosis (No. 18) in terms of EDV, PSV and RI retrospectively, we found EDV and PSV to be significantly lower and RI to be significantly higher (P < 0.05). Conclusion: Detection of a decrease in cerebral blood flow in neonates in the first 12 h postpartum has a prognostic value.